Analyse diachronique et synchronique des espaces industrialo-urbains : l’élaboration d’un indicateur d’urbanité. Une étude sur 170 ans à l’échelle de la Grande Région - Nicolas Greiner (Belgeo, 2025)
Industrial-urban areas, often referred to as “mining towns”, bear witness to a perfect combination of industrialization and urbanization (Roncayolo, 1998a). Developed around village cores, these areas are characterized by high density but low socio-economic diversity. These characteristics made them vulnerable to the industrial restructuring of the 1970s. The aim is to develop a statistical indicator to better define these areas and complement landscape approaches. The methodology is based on demographic data collected over a very long period of time, combined with socio-economic data to create an urban character indicator. The results enable us to differentiate industrial-urban areas from other urban areas, providing a better understanding of their development and characteristics. The study focuses on the Greater Region, a cross-border cooperation area representative of industrial history and urban growth in Western Europe.